2000
DOI: 10.1016/s1057-0810(00)00052-4
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of planned retirement age

Abstract: Determinants of planned retirement age are analyzed. The prediction equation indicates that planned retirement age increases substantially as people get older, and increases somewhat with higher noninvestment income. Social Security reform should recognize that the capacity to continue working and the ability to afford to retire both influence the age at which people plan to retire. The range of planned retirement ages suggests that research on the adequacy of retirement preparation should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 16 publications
1
34
0
Order By: Relevance
“…Besides, Lee and Law (2004) concluded that individuals are more motivated to take action for retirement as their age and income increases. This statement is supported by Montalto, Yuh and Hanna (2000) where as they found that planned retirement age are guided by reinforcement given from constant visit or review on the information needed for planning.…”
Section: Agementioning
confidence: 90%
“…Besides, Lee and Law (2004) concluded that individuals are more motivated to take action for retirement as their age and income increases. This statement is supported by Montalto, Yuh and Hanna (2000) where as they found that planned retirement age are guided by reinforcement given from constant visit or review on the information needed for planning.…”
Section: Agementioning
confidence: 90%
“…Generally speaking, planning for retirement is a complex and long-lasting process and is often subject to adjustments over time, be it due to changes in national pension regulations, changes in health or altered financial conditions (Montalto et al 2000). Despite the complexity of this particular topic, however, retirement expectations of individuals are solid and comply with actual retirement outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Individual Retirement Accounts (IRAs) and Keogh plans allow workers to accumulate retirement savings without paying taxes on the contributions or the earnings on the contributions until they retire. These savings help individuals feel confident that they will have enough money during retirement (DeVaney & Chien, 2001;DeVaney & Su, 1997;Hatcher, 2002;Montalto, Yuh, & Hanna, 2000).…”
Section: Explanatory Factors and Hypothesesmentioning
confidence: 99%
“…While liquid assets can satisfy the need for liquidity, investment assets and real assets were included to capture long-term goals, especially retirement goals (Montalto et al, 2000). Thus, this study included three types of assets to measure the effects of short-term funds, long-term assets, and long-term assets that relate to quality of life (e.g., homes).…”
Section: Independent Variablesmentioning
confidence: 99%